Pelatihan Penggunaan Aplikasi Penjualan - Tri Darma Rosmala Sari; Dwi Tirta Kencana; Meiza Anjelita (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2023)
Lampung Province, especially in the Natar sub-district, South Lampung regency, has a large and varied number of MSMEs, which are spread across various villages in the sub-district. Based on the results of interviews with the administrators of the MSME community, Natar explained that the average MSME sales record was still done manually and they could not immediately know the total number of sales that occurred during one period and they also could not know the amount of existing inventory, so that UMKM could not quickly calculate how much profit they have made and it is difficult to decide when to produce goods, because it is difficult to see how many goods are still available. The expected outputs from this PKM activity are scientific articles published in community service journals, training videos, and news published in newspapers. Stages in the implementation of activities namely planning, action, observation and reflection. The activities will be carried out for 6 months, starting in early December and ending in May 2022. The activities that will be offered are in the form of training using sales and inventory recording applications. The target of this activity is MSMEs that are members of the Natar MSME community, South Lampung.